Nitrogen‐Doped Graphene Aerogels for Supercapacitors: Advances in synthesis and electrochemical performance - Elsehsah, Khaled Abdou Ahmed Abdou; Noorden, Zulkarnain Ahmad; Mat Saman, Norhafezaidi; Ahmad, Noor Azlinda; Hasan, Mohd Faizal; Ab Ghani, Sharin; Ahmed, Ayaz (John Wiley and Sons Inc, 2026)
Nitrogen‐doped graphene aerogels (NGAs) have attracted much attention as next‐generation electrode materials for super-capacitors because of their high surface area, excellent conductivity, and chemical tunability. Recent studies have confirmed how nitrogen doping can improve pseudocapacitive behaviour, wettability, and electron transport, thus significantly improving the specific capacitance, energy density, and cycling performance. This review analyses the different synthesis strategies, such as hydrothermal self‐assembly, sol‐gel polymerisation, and template‐directed synthesis, and shows the electrochemical performance obtained from both symmetric and asymmetric set‐ups. The best‐performing NGAs have demonstrated specific capacitances reaching 900 F/g, energy densities of over 60 Wh/kg, and long‐term retention exceeding 90% over 10,000 cycles. Nonetheless, multiple synthesis strategies are still limited by batch processing, excessive thermal demand, and difficulty with dopant homogeneity. Details on the electrode configuration and performance reported between studies are inconsistent, making direct comparisons challenging and hindering industrial translation. This review highlights the critical demand for scalable, greener synthesis protocols, standardised testing protocols, and systematic evaluations of the role of nitrogen species in capacitance enhancement. This work can be extended to dual‐doping, flexible electrode fabrication, and the incorporation of the doped material into practical device architectures. Such insights provide a basis for rationally designing high‐performance N‐GAs for supercapacitors.